Frequency of remission achievement in the pre-treat-to-target decade in juvenile idiopathic arthritis - Ana Isabel Rebollo-Giménez; Angela Pistorio; Silvia Maria Orsi; Francesca Ridella; Elena Aldera; Luca Carlini; Valentina Natoli; Marco Burrone; Silvia Rosina; Roberta Naddei; Alessandro Consolaro; Esperanza Naredo; et al. (Pediatric Rheumatology Online Journal)
Abstract Background Over the past two decades there has been a remarkable advance in the management of juvenile idiopathic arthritis (JIA), which has led to considerable improvement in prognosis. In 2018, the introduction of the treat-to-target (T2T) strategy in JIA has been advocated to further ameliorate disease outcome. To provide a benchmark for comparing future outcomes in the “T2T era”, this study investigates the percentage of JIA patients who achieved clinical inactive disease (CID) in the decade that preceded the publication of the T2T recommendations in JIA. Methods The clinical charts of all JIA patients followed at the study center between 2007 and 2017 who were first seen within 6 months after disease onset and had a minimum of 6-month follow-up information available were reviewed retrospectively. The attainment of CID, defined by 2004 Wallace criteria, was assessed cross-sectionally at 6, 12, 24, and 60 months after first observation. Results A total of 394 patients were included. Patients were classified into four “functional phenotypes”: systemic arthritis (7.1%), oligoarthritis (48.2%), polyarthritis (40.4%), and other arthritis (4.3%). The overall frequency of CID was 25.1% at 6 months, 34.5% at 12 months, 44.6% at 24 months, and 49.1% at 60 months. The systemic and oligoarticular subgroups had the highest rates of CID at 6 months (32.1% and 29.5%, respectively) and at 12 months (40% and 41.1%, respectively). At the 60-month evaluation, which was available for 226 out of 394 patients (57.4%), the frequency of CID among patients still followed at study center was 42.9%, 51.7%, 46.7%, and 45.5% for the systemic, oligoarticular, polyarticular, and other arthritis phenotypes, respectively. Conclusion A sizeable proportion of patients treated in the decade preceding the beginning of the “T2T era” and on continued follow-up did not achieve or maintain the state of CID over the long term. Future studies will determine whether the application of the T2T strategy increases the ability to achieve sustained disease quiescence in patients who respond suboptimally to the conventional therapeutic regimens.